Field notes contributed by Hank Zaletel, summer 1981 - Zaletel, Hanket al (1981)
Summer report of birds contributed by Hank Zaletel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1981. Epson - sheet feed